1993
DOI: 10.1002/cne.903370308
|View full text |Cite
|
Sign up to set email alerts
|

An immunocytochemical study of the FMRFamide neuropeptide gene products in Drosophila

Abstract: We have mapped protein expression of the FMRFamide neuropeptide gene in Drosophila with polyclonal antisera against three small peptides whose sequences were derived from the Drosophila proFMRFamide precursor. One antiserum was affinity-purified and extensively characterized. The enriched antibodies labeled 15-21 bilaterally symmetric pairs of neurons in a pattern that corresponded very closely to the pattern of in situ hybridization that was determined previously (Schneider et al. [1991] J. Comp. Neurol. 304:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 41 publications
6
81
1
Order By: Relevance
“…As shown Fig. 5, dissected wild type 1st instar larval brains have a stereotypical pattern of neuroendocrine cells in the ventral ganglion of the central nervous system that produce the FMRF pre-propeptide (52). Dissected 1st instar larval brains from ctr1A 25 maternal and zygotic mutants also show a similar pattern of FMRF prepropeptide producing neuroendocrine cells within the ventral ganglion without qualitative differences in abundance (Fig.…”
Section: Ctr1a Localizes To the Plasma Membrane And To Intracellular mentioning
confidence: 64%
“…As shown Fig. 5, dissected wild type 1st instar larval brains have a stereotypical pattern of neuroendocrine cells in the ventral ganglion of the central nervous system that produce the FMRF pre-propeptide (52). Dissected 1st instar larval brains from ctr1A 25 maternal and zygotic mutants also show a similar pattern of FMRF prepropeptide producing neuroendocrine cells within the ventral ganglion without qualitative differences in abundance (Fig.…”
Section: Ctr1a Localizes To the Plasma Membrane And To Intracellular mentioning
confidence: 64%
“…In total, 17 different DrmFMRFamide cell types might exist. 8 Several studies have shown the existence of at least three different enhancers in …”
Section: The Fmrfamide Precursormentioning
confidence: 99%
“…The Drosophila FMRFamide gene encodes eight neuropeptides, the most abundant of which is DPKQDFMRFamide (Schneider et al, 1993). Many Drosophila GPCRs sensitive to peptides structurally related to FMRFamide have been deorphaned using cell culture assays (Cazzamali and Grimmelikhuijzen, 2002;Nichols, 2006), but their in vivo functions have not been investigated and little is known about their downstream effectors in synapses.…”
Section: Introductionmentioning
confidence: 99%